A Pragmatic Approach to Translation: A Study of Deixis in the Glass Menagerie - Shna Ihsan Izzadeen; Suhayla H. Majeed (Zanco Journal of Humanity Sciences)
Language is a fact that links various cultures and a way of describing feelings and ideas that people try to convey. Literary Translation can act as a very useful approach to innovate our culture to the world and to decide an adequate place for ourselves inside the global multicultural relatedness. Translation is an attempt of transferring equivalent meaning of a text from source language into target language. The study aims to identify types of deixis and identify the similarities and differences in the play “Glass Menagerie” written by Tennesser Williams and its Kurdish translation “Giyanlebere Şuşeyyekan *(see appendix) that is translated by Dr. Azad Hama Sharif. The study uses a descriptive and qualitative method, for identifying and analyzing types of deixis which are person deixis, place deixis, time deixis, discourse deixis and social deixis. The study is based on Levinson's theory on deixis (1983). To analyze the play, the first step was reading the play, then finding the types of deixis, and lastly describing the equivalence of deictic words in target text. To conclude that the researcher will point out the pragmatic functions of person deixis, place deixis, time deixis, discourse deixis and social deixis of English and Kurdish, and also pointing out similarities and differences. Thus the usage of deixis in daily life is very important, because it avoids the misinterpretations of the speakers and the addressees.